EKSISTENSI SIDANG VIRTUAL ONLINE MENURUT KACAMATA HUKUM PIDANA DI INDONESIA - Herman Sitompul (Res Justitia : Jurnal Ilmu Hukum, 2021)
Indonesia is a rule of law, where the laws and regulations put forward by Hans Kelsen, namely the theory of legal levels (Stufentheorie). This theory emphasizes that in the hierarchy of existing laws and regulations, they should not conflict with existing regulations. Hans Kelsen's theory is in line with the principle of the law of lex superior derogat legi inferiori, which emphasizes that the law under it must not conflict with the law above it. The existence of an online or online virtual trial during the Covid 19 Pandemic in Indonesia has become a polemic in the community. This is because most Indonesians think that this does not have a constitutional basis, so that many defendants refuse to be tried virtually online or online. On that basis, the author is interested in examining the extent of the existence of an online or online virtual trial according to the point of view of criminal law through a paper in this journal.